Long-range and high-resolution distributed Brillouin fiber sensors Capteur Brillouin réparti à fibre optique à haute résolution et longue portée - Sylvestre, Thibaut; Lee, Min Won; Nguyen, Duc Minh; Stiller, Birgit; Beugnot, Jean Charles; Maillotte, Hervé; Hauden, Jérôme; Thévenaz, Luc (Instrumentation Mesure Metrologie, 2013)
Brillouin-based distributed optical fiber sensors have been the subject of intense research in recent years because they offer a unique solution for continuous, real-time monitoring in civil engineering and petroleum industry. These sensors provide strain or temperature measurements with meter spatial resolution over several tens of kilometers. In this work we demonstrate two new Brillouin fiber sensors with enhanced performances based on advanced modulation formats from high-speed lightwave communications systems. We first report a Brillouin distributed sensor with enhanced centimeter resolution using a digital phase-shift keying technique. The second one uses a quadrature phase-shift keying modulator as a single-sideband modulator to balance the pump depletion and the fiber loss by the Brillouin gain. Combined with a specially-designed in-line bidirectional Erbium-doped fiber amplifier, we demonstrate that this technique allows for the achievement of long-range distributed sensing over 100 km. © 2013 Lavoisier.
CRIS-Team Scopus Importer:2021-06-29
Keywords: Brillouin optical time domain analysis; Distributed fiber sensors